PENDAMPINGAN PENINGKATAN KOMPETENSI GURU DALAM PERANCANGAN PEMBELAJARAN KOLABORATIF BERBASIS KEARIFAN LOKAL TERINTEGRASI PLATFORM DIGITAL DI UPT SPF SDN 101797 - Nurmayani; Yusron Abda’u Ansya; Halimatussakdiah; Hapni Laila Siregar; Nurhairani; Sugianto (Universitas Negeri Medan, 2026)
Abstract: This community service activity is motivated by the still low competence of teachers in designing collaborative learning based on local wisdom integrated with digital platforms, as well as the dominance of conventional teacher-centered learning. The objective of this activity is to enhance teachers' competencies in designing and implementing innovative learning based on technology and local context. The implementation method uses a participatory mentoring approach and learning by doing thru the stages of preparation, implementation, monitoring and evaluation, as well as follow-up. The subjects of the activity are teachers from UPT SPF SDN 101797, conducted within the partner school environment. Data collection techniques include observation, interviews, questionnaires, and documentation, while data analysis uses qualitative and quantitative descriptive methods. The results of the activities show an increase in teachers' competencies in collaborative learning from 48% to 87%, integration of local wisdom from 55% to 88%, digital literacy from 40% to 82%, and the use of digital platforms from 40% to 86%. The quality of learning devices improved from 58% to 88% and the effectiveness of learning from 52% to 85%. In conclusion, these activities effectively significantly enhance teachers' competencies and promote a more innovative, collaborative, and sustainably digital-based transformation of learning. Keyword: Collaborative Learning, Local Wisdom, Digital Literacy, Digital Platforms, Teacher Competence Abstrak: Kegiatan pengabdian kepada masyarakat ini dilatarbelakangi oleh masih rendahnya kompetensi guru dalam merancang pembelajaran kolaboratif berbasis kearifan lokal yang terintegrasi platform digital, serta dominannya pembelajaran konvensional yang berpusat pada guru. Tujuan kegiatan ini adalah meningkatkan kompetensi guru dalam merancang dan mengimplementasikan pembelajaran inovatif berbasis teknologi dan konteks lokal. Metode pelaksanaan menggunakan pendekatan participatory mentoring dan learning by doing melalui tahapan persiapan, pelaksanaan, monitoring dan evaluasi, serta tindak lanjut. Subjek kegiatan adalah guru UPT SPF SDN 101797 yang dilaksanakan di lingkungan sekolah mitra. Teknik pengumpulan data meliputi observasi, wawancara, kuesioner, dan dokumentasi, sedangkan analisis data menggunakan deskriptif kualitatif dan kuantitatif. Hasil kegiatan menunjukkan peningkatan kompetensi guru pada pembelajaran kolaboratif dari 48% menjadi 87%, integrasi kearifan lokal dari 55% menjadi 88%, literasi digital dari 40% menjadi 82%, serta penggunaan platform digital dari 40% menjadi 86%. Kualitas perangkat pembelajaran meningkat dari 58% menjadi 88% dan efektivitas pembelajaran dari 52% menjadi 85%. Kesimpulannya, kegiatan ini efektif meningkatkan kompetensi guru secara signifikan dan mendorong transformasi pembelajaran yang lebih inovatif, kolaboratif, dan berbasis digital secara berkelanjutan. Kata Kunci: Pembelajaran Kolaboratif, Kearifan Lokal, Literasi Digital, Platform Digital, Kompetensi Guru